Ayat-Ayat Al-Qur'an dan hadis-Hadis Tematik Tentang Uang Dan Pembiayaan - M. Iqbal (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
In general money is part of wealth, jewelry and happiness in the world. Money iseverything that is widely accepted as a medium of exchange, while it functions as astandard measure of the value of prices and media for the storage of wealth. While capitalis a property that can be developed in various circumstances to obtain profits. This paperwill explain how money is in the perspective of Alquran and Hadith. Besides that, it alsolinks money with financing. The money cannot stand alone to develop without beingdistributed as working capital. This paper will describe how the Koran sits money ineconomic activities and so also in the hadiths describing both.